2014
DOI: 10.1371/journal.pone.0089596
|View full text |Cite
|
Sign up to set email alerts
|

Highly Immunoreactive IgG Antibodies Directed against a Set of Twenty Human Proteins in the Sera of Patients with Amyotrophic Lateral Sclerosis Identified by Protein Array

Abstract: Amyotrophic lateral sclerosis (ALS), the most common adult-onset motor neuron disorder, is characterized by the progressive and selective loss of upper and lower motor neurons. Diagnosis of this disorder is based on clinical assessment, and the average survival time is less than 3 years. Injections of IgG from ALS patients into mice are known to specifically mark motor neurons. Moreover, IgG has been found in upper and lower motor neurons in ALS patients. These results led us to perform a case-control study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 58 publications
0
27
0
1
Order By: Relevance
“…Seminal studies in the 1980s showed that ALS patients have a high frequency of monoclonal paraproteinemia (115) and a high incidence of autoimmune disorders (116). Numerous IgG antibodies and complement proteins are found in sera (117) from ALS patients, and antibody titer was positively associated with increased disease severity (118). Monoclonal Igs were detectable in 60% of sporadic ALS patients (119), and autoantibodies against ganglioside GM1 and GD1a (120), sulfoglucuronylparagloboside (121), neurofilament proteins (121), the TNF receptor family member FAS (CD95) (122), and voltage-gated Ca 2+ channels (123,124) have all been reported, indicating that ALS patients generate antibody responses to a variety of autoantigens.…”
Section: Inflammation and Autoimmunity In Als/ftdmentioning
confidence: 99%
“…Seminal studies in the 1980s showed that ALS patients have a high frequency of monoclonal paraproteinemia (115) and a high incidence of autoimmune disorders (116). Numerous IgG antibodies and complement proteins are found in sera (117) from ALS patients, and antibody titer was positively associated with increased disease severity (118). Monoclonal Igs were detectable in 60% of sporadic ALS patients (119), and autoantibodies against ganglioside GM1 and GD1a (120), sulfoglucuronylparagloboside (121), neurofilament proteins (121), the TNF receptor family member FAS (CD95) (122), and voltage-gated Ca 2+ channels (123,124) have all been reported, indicating that ALS patients generate antibody responses to a variety of autoantigens.…”
Section: Inflammation and Autoimmunity In Als/ftdmentioning
confidence: 99%
“…Additionally, a study published by May et al (2014), using the same microarray platform as well as a similar biomarker discovery strategy identified 20 differentially expressed autoantibodies with the potential to distinguish amyotrophic lateral sclerosis (ALS) samples from healthy controls. Twenty ALS serum samples were differentiated from 20 control samples with a sensitivity of 99.9%, and a specificity of 100.0%, thus validating the use of Invitrogen's human protein microarray as a biomarker discovery platform as well as confirming the utility of Random Forest in biomarker verification (May et al, 2014).…”
Section: Disease-specific Autoantibody Profiles Using Human Protein Mmentioning
confidence: 99%
“…While these two studies were based on investigations of reactivity to proteins already suggested to be involved in disease pathology, May and colleagues instead used a more unbiased approach. They analyzed serum IgG reactivity toward more than 9000 full-length proteins in 20 ALS and 20 nondiseased controls and identified 20 proteins displaying increased ALS reactivity, several with CNS-related functions [115].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%